Differential impacts of hemolysis on coagulation parameters of blood samples: A STROBE-compliant article. Issue 18 (7th May 2021) - Pan, Lin-Lin; Lee, Ching-Hui; Hung, Kuo-Chuan; Tsai, I-Ting; Wang, Ming-Chung; Sun, Cheuk-Kwan
Abstract : Abstract: This study aimed at investigating the impact of hemolysis on different coagulation parameters. A total of 216 venous blood samples without visible hemolysis were collected from adult patients at a tertiary referral center over six months. The plasma obtained was quantified for six coagulation parameters including prothrombin time, activated partial thromboplastin time, fibrinogen, D-dimer, antithrombin III, and protein C. The rest of the plasma from each blood sample was aliquoted into three tubes, each containing 1 mL of plasma with three different volumes of cell-free hemoglobin (i.e., 2, 4, 8 μL) from lysed RBCs to create simulated hemolyzed blood samples with hemoglobin concentration of approximately 0.1, 0.2, and 0.4 g/dL to mimic mild (1+), moderate (2+), and severe (3+) hemolysis, respectively, before repeating the coagulation tests to determine possible correlation between the simulated degree of hemolysis and the changes in test results of the coagulation parameters. Spearman correlation analysis showed significant decreases in the values of activated partial thromboplastin time, fibrinogen, D-dimer, and protein C values with an increasing degree of simulated hemolysis (all P  < .01). Comparison of the percentage bias of biological variance showed significant positive associations of cell-free hemoglobin concentrations with the percentage bias of D-dimer and protein C. However, only the former was still within the range of biological variance under condition of simulated hemolysis. Besides, the presence of cell-free hemoglobin regardless of concentration had a notable impact on the percentage bias of activated partial thromboplastin time, whereas the influence was non-significant for prothrombin time, fibrinogen, and antithrombin III. The results showed different impacts of simulated hemolysis on six coagulation parameters, highlighting the dependence of clinical reliability on the coagulation parameter to be investigated in hemolytic blood samples.